Urban Nature as an Active Means of Adapting Public Spaces to Climate Conditions: Case Studies from Copenhagen and Selected Polish Cities - Pancewicz, Alina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Progressive climate change brings many challenges to cities, which, in an effort to meet them, are looking for ways to create a built environment that is resilient and adapted to change. The subject of the paper is the urban nature, which, skillfully used and introduced into public space, becomes an active tool for adapting cities to future climate conditions. The aim of the paper is to identify key solutions to introduce urban nature into public spaces in the context of model strategic planning and urban design undertaken in cities.
Keywords: climate adaptation; urban resilience; urban nature; strategic planning; adaptation activities; klimat; przyroda miejska; planowanie strategiczne; działania adaptacyjne